Pregabalin Does Not Reduce Opioid Withdrawal Symptoms: A Randomized Controlled Trial. (December 2019) - Kheirabadi, Gholam R.; Moazeni, Sharyar; Salehi, Mehrdad; Mahaki, Behzad
Abstract : Background and Aim: Controlling the symptoms of opioid withdrawal syndrome is important for the treatment of opioid addiction. There is very limited evidence on the effectiveness of pregabalin on opioid withdrawal syndrome. The present study examines the effectiveness of pregabalin in reducing opioid withdrawal symptoms. Methods: This double-blind clinical-trial was conducted on noninjecting opioid users diagnosed with opioid dependence and referred to the Addiction Treatment Center of Khorshid Hospital in Isfahan, Iran, in 2015 and 2016. The patients were divided into intervention and control groups, and both groups received Buprenorphine for the routine management of opioid withdrawal syndrome. The intervention group additionally received 450 mg/d of pregabalin while the control group received placebos. Opioid withdrawal symptoms were evaluated using the Short Opioid Withdrawal Scale (SOWS). Data were analyzed in SPSS-20. Descriptive data were reported as mean±SD. The analytic data were analyzed using the repeated-measures ANOVA. The level of statistical significance was set at P -value<0.05. Results: The mean age was 41.58±10.09 in the intervention group and 44±8.87 years in the control group ( P =0.47). None of the assessed signs and symptoms differed significantly between the 2 groups. Conclusions: The results did not show the superiority of the 450-mg/day pregabalin regimen versus the placebo for controlling the symptoms of opioid withdrawal syndrome. Further studies administering higher doses of pregabalin are recommended.